1992
DOI: 10.1136/sti.68.6.399
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical urethritis and ascendent genitourinary infections due to sexual stimulation of the urethra by inserted foreign bodies.

Abstract: The cases of 23 men with mechanical urethritis due to insertion of foreign bodies into the urethra are presented. Seven patients had upper urinary tract infections and one died with gangrene of the genitalia and septicaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Pec et al also reported a case series of 23 men presenting with mechanical urethritis and with sepsis and gangrene of the external genitalia due to self-insertion of foreign body [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pec et al also reported a case series of 23 men presenting with mechanical urethritis and with sepsis and gangrene of the external genitalia due to self-insertion of foreign body [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some present with swelling of external genitalia, obstructive symptoms and urinary retention [3]. A long forgotten, self-inflicted foreign body can lead to complications like chronic and recurrent urinary tract infections, encrustations and its attendant complications like obstructive uropathy, vesico-vaginal fistulas, periurethral abscesses, sepsis and even squamous cell carcinoma [3,13].…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…Priapism has also been reported [5,9,13]. A case of death due to gangrene and septicemia after self-insertion of a foreign body was reported by Pec's group [14].…”
Section: A 1bmentioning
confidence: 99%